Evolution of smoking rates among immigrants in France in the context of comprehensive tobacco control measures, and a decrease in the overall prevalence - Sarah Mahdjoub; Mégane Héron; Ramchandar Gomajee; Simon Ducarroz; Maria Melchior; Fabienne El-Khoury Lesueur (BMC, 2023)
Abstract Background The evolution of smoking rates according to migrant status has not been examined in France, despite a recent reduction in overall smoking rates. Methods DePICT is a two waves (2016: n = 4356; 2017: n = 4114) nationwide telephone survey, representative of the French adult population. We compared smoking-related behaviors before and after implementation of tobacco-control measures (2017), according to the geographical region of birth. Results Compared to 2016, individuals originating from Africa or the Middle East had a slightly higher smoking prevalence in 2017 (34.7% vs 31.3%), despite a higher intention to quit or attempt in the preceding year (adjusted OR(ORa) = 2.72[1.90; 3.90]) compared to non-immigrants. They were also less likely to experience an unsuccessful quit attempt (ORa = 1.76[1.18; 2.62]). Conclusion Tobacco-control measures could have widened smoking inequalities related to migrant status. The evolution of smoking-related behaviors among immigrants should be examined when studying the long-term effects of such policies.